Regeneration of Rubus in vitro using forchlorfenuron (CPPU) - Millán Mendoza, B. (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2012)
The ability of N-(2-chloro-4-pyridyl)-N-phenylurea(CPPU),a synthetic compound with cytokinin-like activity, to induce regeneration of whole plants in Rubus was assessed. Regeneration was obtained from internodal segments of three tissue culture recalcitrant red raspberry cultivars Glen Prosen (32%), Glen Moy (38%) and Glen Magna (72%) using media containing low concentrations of CPPU. The ability of CPPU to induce regeneration from the cultivars Taybeny (38%) and Loch Ness (46%) was examined and the results compared with previous work. The regeneration protocol here tested provides the first step for future genetic transformation involving these three Rubus varieties.